MAKING AND TESTING SIMPLE ELECTRICAL CIRCUITS - Fahira Sinaga; Nurhariyati Br Sitepu (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Electricity is essential to us because it's difficult to do normal things without it. It gives us light, and almost all technology requires it to function. This study aims to understand how people learn about series and parallel circuits by conducting simple science experiments. In this study, the authors observed series and parallel circuits during simple activities, using descriptive qualitative methods. The authors conducted this research at STKIP Al Maksum Langkat. The results showed that static electricity occurs when an electric charge remains in one place. Dynamic electricity occurs when an electric charge moves through a wire. In a series circuit, electricity has only one path to flow, so if one part is removed, the entire circuit stops functioning